Activities, access control, and crime: a quasi-experimental study regarding entry gates at train stations in the Netherlands - Lindenbergh, Viviane M. (European journal on criminal policy and research, 2021)
This article discusses a unique “natural experiment,” the introduction of entry gates at Dutch train stations and the potential effects of this on crime in the areas around these stations. A quasi-experimental study was carried out to show that introducing entry gates correlated with a drop in crime in these areas. After entry gates had been introduced, potential offenders could only enter train stations with a valid ticket, which meant that they would be less likely to enter or leave these stations and more likely to choose other places to hang around in or for entering and leaving trains. A dataset was created in which the crime rates around train stations were registered for each month in the years 2013 through 2018. The changing numbers of travelers at each station were also taken into account, as this variable probably correlates with the amount of crime. A two-way fixed-effects model was run on data for about 260 train stations, with and without entry gates, using the relative crime rate per thousand travelers as the dependent variable. Based on this relative crime rate, the use of entry gates was found to coincide with a decrease of 9% in crime, compared to a situation without entry gates. This study can inform policymakers about the potential effects of entry gates in particular and about situational crime prevention in general. Moreover, it illustrates how implementing measures at various locations at different moments enables the effectiveness of such measures to be tested more precisely and with more confidence.